2016
DOI: 10.1007/s12104-016-9685-8
|View full text |Cite
|
Sign up to set email alerts
|

NMR resonance assignments of the major apple allergen Mal d 1

Abstract: The major apple allergen Mal d 1 is the predominant cause of apple (Malus domestica) allergies in large parts of Europe and Northern America. Allergic reactions against this 17.5 kDa protein are the consequence of initial sensitization to the structurally homologous major allergen from birch pollen, Bet v 1. Consumption of apples can subsequently provoke immunologic cross-reactivity of Bet v 1-specific antibodies with Mal d 1 and trigger severe oral allergic syndroms, affecting more than 70 % of all individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…As a first step toward structural characterization, we recently assigned the NMR backbone and side chain 1 H, 13 C, and 15 N chemical shifts of the isoform Mal d 1.0101. 16 Mal d 1.0101, initially cloned from ‘Granny Smith’ apples, and Mal d 1.0102, from ‘Golden Delicious’, were the first isoforms for which the DNA sequence was determined and are identical at the amino acid level. 4 , 17 Here we report the NMR solution structure of this protein.…”
Section: Introductionmentioning
confidence: 99%
“…As a first step toward structural characterization, we recently assigned the NMR backbone and side chain 1 H, 13 C, and 15 N chemical shifts of the isoform Mal d 1.0101. 16 Mal d 1.0101, initially cloned from ‘Granny Smith’ apples, and Mal d 1.0102, from ‘Golden Delicious’, were the first isoforms for which the DNA sequence was determined and are identical at the amino acid level. 4 , 17 Here we report the NMR solution structure of this protein.…”
Section: Introductionmentioning
confidence: 99%
“…Apple allergy manifests various clinical symptoms mediated by an IgE-response, such as respiratory, cutaneous and gastrointestinal disturbances to systemic anaphylaxis [29]. The principal apple allergens, identified so far, are: Mal d 1, a pathogenesis-related protein (PR-10) [30][31][32][33], Mal d 2, a thaumatin-like protein (TLP) [33,34], Mal d 3, a lipid transfer protein (LTP) [33,35] and Mal d 4, a profiling protein [33,36]. All mentioned allergic proteins were found in the apple samples used in this work, both before and after CPLLs treatment, confirming their moderate abundance directly detectable via MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms are Cor a 1.0401 (AF136945), Cor a 1.0402 (AF323973), Cor a 1.0403 (AF323974), and Cor a 1.0404 (AF323975) (Hirschwehr et al 1992), which share a sequence identity of about 97% among each other, and only about 63 and 66% to the pollen allergens Cor a 1.01 and Bet v 1.0101 (Gajhede et al 1996), respectively. The PR-10 food allergens from apple (Malus domestica) Mal d 1.0101 (Ahammer et al 2017(Ahammer et al , 2016 and peach (Prunus 0persica) Pru p 1.0101 (Führer et al 2019), which show the highest birch pollen associated food hypersensitivity along with Cor a 1.04, have sequence identities of 62-64% to the four Cor a 1.04 isoforms. Using an enzyme allergosorbent test, it was shown that the various Cor a 1.04 proteins significantly differ with respect to their IgE-reactivity, resulting Cor a 1.0402, c Cor a 1.0403, and d Cor a 1.0404 (each 0.5 mM) in 20 mM sodium phosphate (pH 6.9) and 2 mM DTT, supplemented with 10% D 2 O at 25 °C.…”
Section: Biological Contextmentioning
confidence: 99%